Comparison of the Changing in Oxygen Saturation that is Induced Bupivacaine and Bupivacaine-Fentanyl in Spinal Anesthesia of Caesarian Section Patient - Fila Apriliawati; Mulyo Hadi Sudjito; Bambang Sukilarso Sakiman (Nexus Kedokteran Klinik, 2015)
ABSTRACT Background: Bupivacaine and Bupivacaine-Fentanyl mostly used in spinal anesthesia for prgenancy that need caesarian sections. Bupivacaine and Bupivacaine-Fentanyl influenced haemodynamic condition. One of the haemodynamic is respiration rate. When the respiration rate changed, it could change the oxygen saturation. Methods: Pregnant patients that need caesarean section with spinal anesthesia bupivacaine and bupivacaine-fentanyl were gathered. During the operation, oxygen saturation was observed with bed site monitor and it was noted. The data of oxygen saturation, data from medical record (age, weight, and height), and data of the previous research (bed site monitor) to be analyzed with Mann-Whitney test, Discriminant test, and Saphiro-Wilk test. Result: According to statistic analysis, there were no significant differences on the changing of oxygen saturation that is induced bupivacaine and bupivacaine-fentanyl in every phase (p >0.050 ). And, there were also no significant differences in the changing of oxygen saturation that was correlated with age (p=0.991), weight (p=0.986), and height (p=1.000). Conclusion: There were no diferrences on the changing of oxygen saturation that is induced bupivacaine and bupivacaine-fentanyl in the spinal anesthesia of caesarian section. There were no correlation also between age, weigth, and height because the homogenity of the sample.